Beatrice and Virgil a novel - Martel, Yann 1963- (Spiegel & Grau, 2010)
When Henry receives a letter from an elderly taxidermist, it poses a puzzle that he cannot resist. As he is pulled further into the world of this strange and calculating man, Henry becomes increasingly involved with the lives of a donkey and a howler monkey--named Beatrice and Virgil--and the epic journey they undertake together.
Keywords: Authors -- Fiction; Taxidermists -- Fiction; Animals -- Fiction; Psychological fiction; Theaterstück; Fiktionale Darstellung